Intermediate-term outcomes of Aurolab aqueous drainage implant in refractory paediatric glaucoma. Issue 7 (4th October 2019) - Puthuran, George Varghese; Palmberg, Paul Frederic; Wijesinghe, Hiruni Kaushalya; Pallamparthy, Srilekha; Krishnadas, SR; Robin, Alan L
Abstract : Aim: To report the intermediate-term outcomes of Aurolab aqueous drainage implant (AADI) surgery in paediatric eyes with refractory glaucoma. Methods: Case records of patients below 18 years, who underwent AADI surgery between 2012 and 2015 with > 2 years follow-up, were analysed. The intraocular pressure (IOP), visual acuity, number of antiglaucoma medications, complications and resurgery if any were recorded at baseline, day 1and then at months 1, 3, 6, 9, 12, 18, 24 and at the last visit. Failure was defined as IOP >18 mm Hg or not reduced by at least 30% below baseline, IOP ≤5 mm Hg on two consecutive follow-up visits after 3 months, reoperation for a complication or loss of light perception vision. Results: 101 eyes of 101 patients were included with a mean age of 10.4±4.7 years at the time of surgery and a mean follow-up of 40.9±15.1 months. Glaucoma following cataract surgery was the most common type of glaucoma (n=31, 30%), followed by primary congenital glaucoma (n=29, 29%). The cumulative probability of failure was 15.8% (95% CI 10.1% to 24.5%) at 1 year, 22.7% (95% CI 15.7% to 32.2%) at 2 years, 42.5% (95% CI 32.6% to 53.9%) at 3 years and 62.1% (95% CI 49.5% to 74.8%) at the 4 years time point. Conclusion: The AADI showed excellent success until 2 years after surgery in paediatric eyes after which failure rates increased. Further prospective studies with longer follow-up are required to evaluate the long-term success of the AADI for paediatric glaucomas.